Cord and method for manufacturing same

By using para-aramid fibers with large crystal size and high crystallinity into strands with different fibers, the problem of large deformation of the tire cord under external force is solved, and the excellent mechanical properties and low creep strain of the cord are achieved.

CN119546807APending Publication Date: 2025-02-28KOLON INDUSTRIES INC

Patent Information

Application Number
CN202380053455.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-01
Filing Date
2023-08-30
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing tire cords are deformed greatly under external forces, making it difficult to meet the mechanical performance requirements of certain applications.

Method used

Para-aramid fibers with large crystal size and high crystallinity are used as the constituent material of the cord, and cords with excellent mechanical properties are formed by stranding them with different fibers.

Benefits of technology

The cord is improved with resistance to external force deformation, reduces creep strain, and significantly improves the mechanical properties of the cord.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239226610000281
    Figure BDA0005239226610000281
  • Figure BDA0005239226610000291
    Figure BDA0005239226610000291
  • Figure BDA0005239226610000321
    Figure BDA0005239226610000321
Patent Text Reader

Abstract

The present application relates to a cord comprising para-aramid fibers, a method of manufacturing the same, a reinforcing material comprising the cord, and a tire. Specifically, since the cord comprises para-aramid fibers having a large crystal size and a high degree of crystallinity and thereby exhibiting excellent mechanical properties, which has high resistance to external force deformation, can be effectively used as a tire reinforcing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a cord including para-aramid fiber, a method for manufacturing the same, a composite material (or a reinforced material) including the cord, and a tire. Background Art

[0002] Aramid fibers containing an aromatic dicarboxylic acid component and an aromatic diamine component, particularly para-aramid fibers such as poly(p-phenylene terephthalamide) (PPTA) fibers, have excellent toughness, elastic modulus, and heat resistance and are therefore widely used in industrial applications and clothing material applications. However, mechanical properties such as toughness and elastic modulus are not sufficient for some applications, and efforts have been made to provide fibers with more excellent physical properties.

[0003] At the same time, aramid fibers are also used in tire cords as tire reinforcement materials. For example, nylon fibers and aramid fibers are twisted together twice to produce tire cords. By the way, nylon is a fiber with a relatively low modulus, and its disadvantage is that it is greatly deformed during stretching (external force). On the other hand, since aramid fibers have a relatively high modulus, the deformation caused by stretching (external force) is small. The difference in these characteristics is due to the morphology and microstructure of the molecular chains that constitute each fiber. Specifically, aramids with linear polymer chains have a relatively high crystallinity due to the hydrogen bonds between the molecular chains, and therefore have a high modulus.

[0004] In view of these points, there is a need to develop an aramid fiber having an improved microstructure and an article (eg, a cord) including the fiber so that the tire cord can show small deformation under an external force. Summary of the invention

[0005] Technical issues

[0006] An object of the present application is to provide an article (eg, a cord) including, as a component, a para-aramid fiber having a large crystal size and a high crystallinity, thereby exhibiting excellent mechanical properties (eg, tensile properties).

[0007] Another object of the present application is to provide a tire cord having excellent mechanical properties (eg, tensile properties).

[0008] Still another object of the present application is to provide a tire cord having high resistance to deformation when an external force is applied, for example, having low creep strain (%).

[0009] All of the above objects and other objects of the present application can be solved by the present application described in detail below.

[0010] Technical Solution

[0011] According to a specific embodiment of the present application, there are provided a cord including two different types of primary twisted yarns, wherein one primary twisted yarn is formed by imparting twist to a para-aramid fiber satisfying predetermined characteristics; and a method for manufacturing the cord.

[0012] Specifically, the inventors of the present application discovered through experiments that, for example, when para-aramid fiber having excellent mechanical properties (e.g., tensile properties) is used in the manufacture of cords used as tire reinforcement materials, etc., the cords formed to include the para-aramid fiber of the present application described below can exhibit excellent mechanical properties (e.g., stiffness, toughness and / or elongation) and have lower creep strain than the cords (under different circumstances), and completed the invention of the present application.

[0013] As used in this specification, the term "cord" may refer to a product including at least two or more different fibers. For example, the cord may refer to a hybrid cord including at least two different primary twisted yarns. Such a cord may be a plied yarn formed by twisting two or more primary twisted yarns together (i.e., secondary twisting).

[0014] In a specific embodiment of the present application, the cord may be a raw cord or an impregnated cord. An impregnated cord refers to a coating agent such as an adhesive applied to a fiber (plied yarn). Conversely, a cord comprising at least two or more fibers without a coating agent applied to the fiber may be referred to as a raw cord. In a specific embodiment of the present application, the cord has a plied yarn structure in which at least a first primary twist yarn and a second primary twist yarn are secondarily twisted together (i.e., made by twisting the primary twist yarns).

[0015] As used in this specification, the term "primary twist" refers to twisting yarns or filaments in any direction, and the term "primary twist yarn" may refer to a single yarn made by twisting yarns or filaments in any direction, that is, a single yarn. Although not particularly limited, the primary twist may refer to, for example, twisting in a clockwise direction or a counterclockwise direction.

[0016] In addition, the term "plied yarn" used in this specification may refer to a yarn made by twisting two or more primary twisted yarns together in any direction. The term "secondary twist" may refer to twisting in the opposite direction to the twisting for primary twisting. For example, secondary twisting may refer to twisting in a clockwise direction or a counterclockwise direction.

[0017] The first twisted yarn or the plied yarn made by imparting twist in any direction may have a predetermined twist number. At this time, the term "twist number" refers to the number of twists per 1 meter, and its unit may be TPM (twist per meter).

[0018] Hereinafter, the cord of the present application and the method for manufacturing the same will be described in more detail.

[0019] In one embodiment of the present application, the present application relates to a cord including para-aramid fiber. Although not particularly limited, the cord can be used as a rubber reinforcing material, more specifically, a tire reinforcing material.

[0020] Specifically, the cord may be formed by plying a para-aramid fiber (A) satisfying the following properties and a different fiber (B) different from the para-aramid fiber.

[0021] Specifically, the para-aramid fiber used to form the cord is a para-aramid fiber having the following properties: (i) a crystallinity of 67% or more, (ii) an apparent crystal size based on a 110 plane of 5.8 to 7.0 nm, (iii) a total fineness of 200 to 1,600 denier, and (iv) a tenacity of 22 g / d or more.

[0022] Unless otherwise specified in this specification, the measured values ​​of physical properties such as tensile properties and microstructure of para-aramid fibers are measured values ​​of the fibers obtained after normal spinning, coagulation and drying, and these measured values ​​are measured values ​​of the fibers without any possible heat treatment process that can be added to the fiber production process.

[0023] When a cord is manufactured by plying a para-aramid fiber (A) having a large crystal size and a high degree of crystallinity and thus exhibiting excellent mechanical properties (e.g., tensile properties) with a different fiber (B) as described above, a cord having excellent mechanical properties (e.g., stiffness, toughness and / or elongation) and low creep strain (%) can be provided, as confirmed in the test described below.

[0024] In an exemplary embodiment, the para-aramid fiber having the above-mentioned characteristics can be formed from a para-aramid polymer prepared by a predetermined polymerization method. Specifically, the para-aramid fiber can be provided by a method for producing para-aramid fiber, the method comprising: a step of filtering a reaction raw material to remove impurities; a step of adding an aromatic diamine to a mixed solvent containing an organic solvent and an inorganic salt to form a slurry; a step of adding an aromatic diacid halide to a reactor containing the slurry three or more times and reacting the mixture to form a para-aramid polymer; and a step of spinning a spinning solution containing the para-aramid polymer to produce a fiber, wherein, in the step of forming the polymer, during the first addition and the second addition of the aromatic diacid halide, the difference between the cooling water temperature at the cooling water inlet side and the cooling water outlet side for cooling the reactor is controlled within 50°C.

[0025] The above production method can minimize the residual amount of inorganic impurities in the final para-aramid polymer through the step of removing impurities from the reaction raw materials, thereby providing a para-aramid fiber having excellent mechanical strength.

[0026] The reaction raw materials include organic solvents, inorganic salts, aromatic diamines and aromatic diacid halides. In the step of filtering the reaction raw materials to remove impurities, at least one of the listed reaction raw materials can be filtered to remove impurities contained in the raw materials. For example, in the step of filtering the reaction raw materials to remove impurities, the reaction raw materials from which impurities have been removed can be prepared by filtering each of the organic solvents, inorganic salts, aromatic diamines and aromatic diacid halides.

[0027] In the step of filtering the reaction raw materials to remove impurities, a filter having a diameter of 0.01 to 1.0 μm, 0.03 to 0.7 μm or 0.05 to 0.5 μm can be used to filter the reaction raw materials. The diameter can be the major axis length of the filter pores of the filter. By using a filter having such a diameter, the content of inorganic impurities in the reaction system can be reduced to less than 1 ppm. In addition, by using a filter having the above-mentioned diameter, the content of inorganic impurities in the polymerized polymer can be reduced to less than 50 ppb. The lower limit of the content of inorganic impurities can be more than 0 ppb.

[0028] The order of performing the step of filtering the reaction raw materials to remove impurities is not particularly limited. Specifically, the step of filtering the reaction raw materials to remove impurities can be performed before the step of forming the slurry, or can be performed during the step of forming the slurry. As an example, if the step of filtering the reaction raw materials to remove impurities is performed during the step of forming the slurry, the organic solvent and the inorganic salt are mixed, and then the mixture is filtered to prepare a mixed solvent, and the aromatic diamine from which the impurities have been removed can be added thereto to form a slurry.

[0029] On the other hand, in the step of forming the slurry, an inorganic salt may be added to the organic solvent to prepare a mixed solvent in order to increase the polymerization degree of the para-aramid polymer.

[0030] The inorganic salt contained in the mixed solvent may include an alkali metal halide or an alkaline earth metal halide. In one example, the inorganic salt may include a salt selected from CaCl 2 , at least one of LiCl, NaCl, KCl, LiBr and KBr. Based on the total weight of the mixed solvent, the content of the inorganic salt may be 0.01 to 15 wt %, 0.05 to 13 wt %, 0.1 to 11 wt % or 1 to 10 wt %.

[0031] The organic solvent contained in the mixed solvent may include at least one selected from N-methyl-2-pyrrolidone, N,N-dimethylacetamide, hexamethylphosphoramide, N,N,N',N'-tetramethylurea, N,N-dimethylformamide and dimethyl sulfoxide. Based on the total weight of the mixed solvent, the organic solvent may be contained in a residual amount other than the inorganic salt.

[0032] In the step of forming the slurry, the mixed solvent and the aromatic diamine may be mixed so that the content of the aromatic diamine in the slurry is 0.5 to 10 wt %. As the aromatic diamine, at least one selected from p-phenylenediamine, 4,4′-oxydianiline, 2,6-naphthalenediamine, 1,5-naphthalenediamine, 4,4′-diaminobenzanilide, etc. may be used.

[0033] Subsequently, in the step of forming the para-aramid polymer, an aromatic diacid halide is added to the previously prepared slurry and reacted to prepare the para-aramid polymer. As the aromatic diacid halide, at least one selected from terephthaloyl dichloride, [1,1′-biphenyl]-4,4′-dicarbonyl dichloride, 4,4′-oxybis(benzoyl chloride), naphthalene-2,6-dicarbonyl dichloride, naphthalene-1,5-dicarbonyl dichloride, etc. can be used.

[0034] Since the aromatic diacid halide and the aromatic diamine react at a molar ratio of 1:1, the molar ratio of the aromatic diacid halide to the aromatic diamine may be about 0.9 to 1.1.

[0035] The polymerization reaction between the aromatic diamine and the aromatic diacid halide proceeds at a fast rate while generating heat. Therefore, generally, a portion of the aromatic diacid halide is first added for prepolymerization, and then the remaining aromatic diacid halide is added to minimize the difference in degree of polymerization between the finally obtained polymers.

[0036] The above-mentioned production method uses reaction raw materials from which more impurities are removed compared with conventional methods, and controls the conditions and method for introducing the reaction raw materials, thereby being able to provide a para-aramid fiber having not only a low polymerization degree difference between polymers but also a large crystal size and a high crystallinity.

[0037] Specifically, in the above production method, the aromatic diacid halide is added in three or more portions instead of the conventional method of adding the aromatic diacid halide in two portions, and the temperature difference between the cooling water entering and leaving the reactor during the first addition and the second addition of the aromatic diacid halide is controlled within 50° C., thereby providing a para-aramid fiber having a desired large crystal size and high crystallinity.

[0038] Specifically, in the step of forming the polymer, a reactor is used into which cooling water can enter and leave.

[0039] In the step of forming the slurry, the slurry may be prepared in the reactor, or the slurry may be prepared in a container outside the reactor and then introduced into the reactor.

[0040] In the step of forming the polymer, the aromatic diacid halide is added to the reactor containing the slurry three or more times. In particular, the aromatic diacid halide may be first added and second added in a state where the difference between the cooling water temperature at the cooling water inlet side and the temperature at the cooling water outlet side is controlled to be 0° C. to 50° C.

[0041] More specifically, during the first addition of the aromatic diacid halide, the temperature difference of the cooling water at the cooling water inlet and the cooling water outlet can be controlled at 0°C to 50°C, 0°C to 40°C, 0°C to 35°C or 0°C to 30°C.

[0042] In order to control the difference between the cooling water temperature at the cooling water inlet side and the temperature at the cooling water outlet side within 50°C, the stirring speed of the reactor can be adjusted to 10 to 1000 rpm, 10 to 900 rpm, 10 to 700 rpm or 10 to 500 rpm while the cooling water is circulating in the reactor.

[0043] The content of the first added aromatic diacid halide may be adjusted to 20 to 40 mol % or 25 to 35 mol % relative to the total content of the aromatic diacid halide added as a whole. Within this range, a prepolymer having a molecular chain of an appropriate length may be formed.

[0044] After the aromatic diacid halide is first added, prepolymerization may be performed by stirring at a temperature of 0° C. to 45° C. for 1 to 30 minutes or 5 to 15 minutes.

[0045] Subsequently, in order to control the difference between the cooling water temperature at the cooling water inlet side and the temperature at the cooling water outlet side to within 50° C. again, the stirring speed of the reactor can be adjusted to 10 to 1000 rpm, 10 to 900 rpm, 10 to 700 rpm or 10 to 500 rpm while the cooling water is circulating in the reactor.

[0046] The content of the second added aromatic diacid halide can be adjusted to 20 to 75 mol%, 40 to 75 mol%, or 50 to 70 mol% relative to the total content of the aromatic diacid halide added as a whole. Within this range, a polymer that can provide a fiber having a large crystal size and high crystallinity while minimizing the difference in degree of polymerization between polymers can be formed.

[0047] After the second addition of the aromatic diacid halide, polymerization may be performed by stirring at a temperature of 0° C. to 45° C. for 1 minute to 30 minutes or 5 minutes to 15 minutes.

[0048] After that, the remaining amount of the aromatic diacid halide is added in one or more portions, and then additional polymerization is performed to finally prepare a para-aramid polymer. The additional polymerization can be performed by stirring at a temperature of 0° C. to 45° C. for 5 minutes to 1 hour or 10 minutes to 40 minutes.

[0049] After the step of forming the polymer, any one or more of a step of separating the obtained polymer from the polymerization reaction system, a step of washing the polymer, a step of neutralizing the polymer, and a step of pulverizing the polymer may be performed regardless of the order.

[0050] The intrinsic viscosity of the para-aramid polymer may be 4.0 dl / g or more, 5.0 dl / g or more, or 5.3 dl / g or more, and 9.0 dl / g or less.

[0051] The intrinsic viscosity deviation of the para-aramid polymer may be 1.0 dl / g or less, 0.9 dl / g or less, or 0.8 dl / g or less. The lower the intrinsic viscosity deviation of the para-aramid polymer, the more advantageous it is, and therefore, the lower limit of the intrinsic viscosity deviation may be 0 dl / g or more.

[0052] The intrinsic viscosity deviation can be determined as follows: the para-aramid polymer that has been washed and dried is divided into a group of 2 mm or more, a group of 1 mm or more and less than 2 mm, and a group of less than 1 mm using standard sieves having mesh sizes of 1 mm and 2 mm, respectively, the intrinsic viscosity of each group is measured, and then the difference between the maximum value and the minimum value of the average intrinsic viscosity of the three groups is calculated.

[0053] Since the para-aramid polymer is made from reaction raw materials with impurities removed, very little or no inorganic impurities remain in the polymer. In one example, the content of inorganic impurities in the polymer may be 50 ppb or less.

[0054] The para-aramid polymer may be poly(p-phenylene terephthalamide), poly(4,4′-benzanilide terephthalamide), poly(p-phenylene-4,4′-biphenylene-dicarbonylamide), poly(p-phenylene-2,6-naphthalene dicarbonylamide), or copolymers thereof. In one example, the para-aramid polymer may be poly(p-phenylene terephthalamide).

[0055] On the other hand, in the step of producing fibers, a spinning solution containing the polymer prepared in the step of forming a polymer is spun to provide fibers.

[0056] As the solvent of the spinning solution, sulfuric acid having a concentration of 97 to 102% by weight can be used. As the above-mentioned solvent, chlorosulfonic acid, fluorosulfonic acid, etc. can also be used instead of sulfuric acid.

[0057] The viscosity of the spinning solution for producing the fiber increases with the increase of the concentration of the para-aramid polymer in the spinning solution. However, when the concentration of the para-aramid polymer exceeds the critical concentration, the viscosity of the spinning solution decreases rapidly. At this time, the spinning solution changes from optically isotropic to optically anisotropic without forming a solid phase. The optically anisotropic spinning solution can provide high-tenacity para-aramid fiber without a separate drawing process due to its structural and functional properties. Therefore, the concentration of the para-aramid polymer in the spinning solution preferably exceeds the critical concentration, but if the concentration is too high, the viscosity of the spinning solution will become too low. Therefore, the spinning solution can contain 10 to 25 weight % of the para-aramid polymer relative to the total weight of the spinning solution.

[0058] In the step of producing the fiber, a spinning step of spinning a spinning solution may be performed.

[0059] In the spinning step, the spinning solution may be spun into filaments by air-gap wet spinning.

[0060] Air gap wet spinning is a method in which an air gap is placed between the spinneret and the coagulation bath surface. According to this air gap wet spinning method, the spinning solution can pass through the spinneret via the air gap and can be spun into the coagulation bath containing the coagulation solution.

[0061] In the spinning step, when the spinning solution is extruded through a spinneret, the thickness of the fiber can be controlled by the pressure and the spinning speed.

[0062] The spinneret may include a plurality of holes through which the spinning solution may be spun.

[0063] Specifically, the spinneret may include 50 to 3000 holes, 100 to 2000 holes, 120 to 1500 holes, or 500 to 1200 holes. Within this range, a para-aramid fiber having a large crystal size and high crystallinity and exhibiting excellent tensile properties can be provided.

[0064] The diameter of the hole formed on the spinneret must be adjusted to an appropriate size, which can improve the molecular orientation of both the surface and the inside of the filament. In this regard, the diameter of the hole of the spinneret can be adjusted to 50 μm or more and 100 μm or less.

[0065] In the spinning step, the spinning solution may be spun at a spinning speed of 80 m / min or more and 800 m / min or less.

[0066] Specifically, the spinning solution can be spun at a spinning speed of 80 to 800 m / min, 100 to 800 m / min, 300 to 800 m / min, 500 to 700 m / min, 550 to 660 m / min, 580 to 650 m / min, 580 to 640 m / min or 590 to 610 m / min. Within this range, a para-aramid fiber having a large crystal size and high crystallinity and exhibiting excellent tensile properties can be provided.

[0067] The spinning solution spun through the spinneret is obtained as unsolidified filaments in which sulfuric acid is distributed on the matrix and the para-aramid polymer is uniformly distributed. Such uncoagulated filaments can be solidified by passing through a coagulation tank containing a coagulation liquid through an air gap.

[0068] The air gap may be an air layer or an inert gas layer. In one example, the air gap may be a layer supplied with dry nitrogen (N 2 ) of nitrogen layer. The length of the air gap can be adjusted from 0.1 to 15 cm.

[0069] The spinning solution spun out from the spinneret and passed through the air gap forms a filament, and sulfuric acid therein is removed during the process of passing through the coagulation tank. At this time, if sulfuric acid is quickly removed from the surface of the filament, the surface of the filament may solidify before the sulfuric acid contained therein is released, which may reduce the uniformity of the inside and outside of the filament. Therefore, the coagulation solution contained in the coagulation tank is preferably an aqueous sulfuric acid solution containing sulfuric acid.

[0070] Specifically, the coagulation liquid contained in the coagulation tank can be an aqueous solution of sulfuric acid in which sulfuric acid is added to water. In addition, as required, a monohydric alcohol (monoalcohol), such as methanol, ethanol and propanol; a dihydric alcohol (glycol), such as ethylene glycol or propylene glycol; or a trihydric alcohol (triol), such as glycerol, can be further added to the coagulation liquid.

[0071] The temperature of the coagulation liquid is preferably 1 to 10° C. If the temperature of the coagulation liquid is too low, sulfuric acid may have difficulty escaping from the filaments. If the temperature of the coagulation liquid is too high, sulfuric acid may quickly escape from the filaments, which may reduce the uniformity of the filaments.

[0072] A condensation tube can be formed at the lower part of the condensation tank. The condensation tube is connected to the condensation tank, and a plurality of injection ports can be formed in the condensation tube. In this case, the injection port is connected to a predetermined injection device so that the condensation liquid ejected from the injection device is ejected onto the filament passing through the condensation tube through the injection port. A plurality of injection ports are preferably aligned so that the condensation liquid is ejected symmetrically relative to the filament. The injection angle of the condensation liquid is preferably 0 to 85 ° relative to the axial direction of the filament. Particularly in commercial production processes, an injection angle of 20 to 40 ° is suitable.

[0073] In the step of producing the fibers, after the coagulation step, a washing step may be performed to remove sulfuric acid remaining in the coagulated filaments.

[0074] The washing step may be performed by spraying water or a mixed solution of water and an alkaline solution onto the solidified filaments.

[0075] The washing step may be performed in multiple stages. For example, the coagulated filaments may be first washed with a 0.1 to 1.5 wt. % aqueous caustic solution, and then second washed with a more dilute aqueous caustic solution.

[0076] In the step of producing the fibers, after the coagulation and washing steps, a drying step may be performed to adjust the remaining moisture content in the filaments.

[0077] The drying step can be carried out by adjusting the contact time of the filaments with the heated drying rollers or by adjusting the temperature of the drying rollers.

[0078] The monofilament constituting the finally obtained para-aramid fiber may have a fineness of 1.0 to 2.5 denier (denier).

[0079] In addition, the para-aramid fiber includes a plurality of monofilaments, and may have a total fineness of 200 to 1,600 denier, 200 to 400 denier, 800 to 1,000 denier, 1,000 to 1,100 denier, or 1,400 to 1,600 denier.

[0080] The para-aramid fiber produced according to the above-mentioned production method has a large crystal size and exhibits high crystallinity and orientation, and thus can exhibit excellent mechanical properties (eg, tensile properties).

[0081] The para-aramid fiber is produced according to the above-mentioned production method, and thus, may have an increased crystal size.

[0082] In one example, the apparent crystal size of the para-aramid fiber based on the 110 plane is 5.8 nm or more, 5.9 nm or more, 6.0 nm or more, 6.1 nm or more, or 6.2 nm or more, and 7.0 nm or less, 6.8 nm or less, 6.7 nm or less, or 6.6 nm or less. In addition, the apparent crystal size of the para-aramid fiber based on the 200 plane is 5.0 nm or more, 5.8 nm or more, or 5.6 nm or more, and 6.5 nm or less, 6.4 nm or less, 6.3 nm or less, or 6.2 nm or less.

[0083] The apparent crystal size is the apparent crystal size analyzed by X-ray diffraction pattern. For more detailed measurement methods, please refer to the method described in the test examples described later. The para-aramid fiber can have high crystallinity because it is produced according to the above production method.

[0084] Specifically, the crystallinity of the para-aramid fiber may be 67% or more, 67.5% or more, 68% or more, 68.5% or more, 69% or more, 69.5% or more, 70% or more, 70.5% or more, 71% or more, 71.5% or more, 72% or more, 72.5% or more, 73.0% or more, 73.5% or more, 74.0% or more, 74.5% or more, 75.0% or more, and 78% or less, 77.5% or less, 77.0% or less, 76.5% or less, 76.0% or less, 75.5% or less, 75% or less, 74.5% or less, 74.0% or less, 73.5% or less, or 73% or less.

[0085] The crystallinity is the crystallinity analyzed by X-ray diffraction pattern. For a more detailed measurement method, please refer to the method described in the test examples described below.

[0086] The para-aramid fiber can exhibit a high degree of orientation due to being produced according to the above production method, that is, the para-aramid fiber can have a high degree of orientation and a small orientation angle.

[0087] In one example, the orientation angle of the para-aramid fiber based on the 110 plane may be 2° or more, 3° or more, 4° or more, 5° or more, 6° or more, or 7° or more. Also, the orientation angle based on the 110 plane may be 12° or less, 11.5° or less, 11° or less, 10.5° or less, 10° or less, 9.5° or less, 9.4° or less, 9.3° or less, 9.2° or less, 9.1° or less, or 9.0° or less. Furthermore, the orientation angle of the para-aramid fiber based on the 200 plane may be 2° or more, 3° or more, 4° or more, 5° or more, 6° or more, 7° or more, or 8° or more. Moreover, the orientation angle based on the 200 plane can be 13° or less, 12° or less, 11.5° or less, 11.4° or less, 11.3° or less, 11.2° or less, 11.1° or less, 11° or less, 10.5° or less, 10.4° or less, or 10.3° or less.

[0088] The orientation angle is an orientation angle analyzed by an X-ray diffraction pattern. For a more detailed measurement method, please refer to the method described in the test example described below.

[0089] Since the para-aramid fiber is produced according to the above-mentioned production method, a paracrystalline parameter can be minimized.

[0090] In one example, the para-aramid fiber may have a minor crystal parameter of 1.00% or more or 1.30% or more, and 1.85% or less, 1.80% or less, 1.70% or less, or 1.60% or less.

[0091] The secondary crystal parameter is a secondary crystal parameter analyzed by an X-ray diffraction pattern. For a more detailed measurement method, please refer to the method described in the test example described below.

[0092] Since the para-aramid fiber has a large crystal size and a high crystallinity, it can exhibit excellent tensile properties.

[0093] In one example, the tenacity of the para-aramid fiber may be 22 g / d or more, 22.5 g / d or more, 23 g / d or more, 23.5 g / d or more, 24 g / d or more, or 25 g / d or more, and 30 g / d or less or 28 g / d or less. In addition, the Young's modulus of the para-aramid fiber may be 750 g / d or more, 760 g / d or more, 780 g / d or more, 790 g / d or more, 800 g / d or more, or 810 g / d or more, and 900 g / d or less, 880 g / d or less, or 860 g / d or less. In addition, the elongation of the para-aramid fiber may be 2.0% or more, 2.5% or more, 3.0% or more, 3.1% or more, 3.2% or more, 3.3% or more, or 3.4% or more, and 4.5% or less or 4.0% or less.

[0094] Tensile properties such as toughness, Young's modulus and elongation are measured according to ASTM D885 standard test method on samples with a twist factor of 1.1. For more detailed measurement methods, please refer to the method described in the test examples described below.

[0095] The cord exhibits different characteristics (physical properties) depending on its thickness. For example, if the cord is used as a tire reinforcement material, a thicker cord improves tire performance in terms of stiffness and modulus, but the thickness of the rubber covering the top and bottom of the fabric increases and the tire size increases, resulting in an increase in weight. Therefore, it is not suitable for tires where fuel efficiency and weight reduction are important. In addition, when the thickness of the cord is thin, it is beneficial to reduce the weight of the tire, but the stiffness and modulus are reduced, so that the cord cannot fully exhibit its performance as a reinforcement material. In the present application, taking this into account, the fineness of the fibers forming the cord (each fiber forming the primary twisted yarn) is appropriately adjusted.

[0096] In an exemplary embodiment, the fineness of the para-aramid fiber or the first twisted yarn (first first twisted yarn) formed therefrom may be 200 to 1600 deniers (denier). For example, the lower limit of the fineness of the para-aramid fiber may be 300 deniers or more, 400 deniers or more, 500 deniers or more, 600 deniers or more, 700 deniers or more, 800 deniers or more, 900 deniers or more, 1000 deniers or more, or 1100 deniers or more, and the upper limit may be, for example, 1500 deniers or less, 1400 deniers or less, 1300 deniers or less, 1200 deniers or less, 1100 deniers or less, or 1000 deniers or less. Although not particularly limited, para-aramid fibers of 900 to 1100 deniers or 1400 to 1600 deniers may be used as the first twisted yarn.

[0097] In an exemplary embodiment, the fineness of the dissimilar fiber or the first twisted yarn (second first twisted yarn) formed therefrom can be 600 to 2000 deniers (denier). For example, the lower limit of the fineness of the dissimilar fiber can be 650 deniers or more, 700 deniers or more, 750 deniers or more, 800 deniers or more, or 850 deniers or more. And, the upper limit can be, for example, 1900 deniers or less, 1800 deniers or less, 1700 deniers or less, 1600 deniers or less, 1500 deniers or less, 1400 deniers or less, 1300 deniers or less, 1200 deniers or less, 1100 deniers or less, 1000 deniers or less, or 900 deniers or less. Although not particularly limited, dissimilar fibers of 700 to 900 deniers or 1100 to 1400 deniers can be used as the first twisted yarn.

[0098] There is no particular limitation on the type of different fiber (B) that is twisted together with the para-aramid fiber (A) to form the cord, but for example, nylon fiber or polyester fiber can be used to make the cord. That is, the cord of the present application can be formed by twisting a primary twist yarn containing para-aramid fiber and a primary twist yarn containing different fiber (such as nylon fiber or polyester fiber).

[0099] The degree of twisting of the primary twisted yarn and / or the degree of twisting (i.e., secondary twisting) between the primary twisted yarns affect the physical properties of the cord. Generally, when the twist is high, the cord has a spiral inclination in the vertical direction, so that the elongation (or elongation at break, or intermediate elongation) increases and the modulus decreases, and an external force is applied due to the twist, thereby reducing the toughness (or stiffness). On the contrary, when the twist is low, the fibers are well arranged in the direction of the cord (the spiral inclination value in the vertical direction of the cord is low), so that compared with high twist, the toughness (or stiffness) and modulus increase, but the elongation is low. In the present application, taking the above points into consideration, the number of twists of each primary twisted yarn and the number of twists between the primary twisted yarns can be adjusted.

[0100] In an exemplary embodiment, (A) the para-aramid fiber may be a pre-twisted yarn (first pre-twisted yarn) imparted with a twist of 250 to 600 TPM, and (B) the different fiber may be a pre-twisted yarn (second pre-twisted yarn) imparted with a twist of 250 to 600 TPM. And, the cord may be formed by secondarily twisting the first pre-twisted yarn and the second pre-twisted yarn together.

[0101] In a specific embodiment of the present application, the twist number (first twist number) of the first primary twist yarn comprising (A) para-aramid fiber and the twist number (second twist number) of the second primary twist yarn comprising (B) different fibers may be 260 TPM or more, 270 TPM or more, 280 TPM or more, 290 TPM or more, 300 TPM or more, 310 TPM or more, 320 TPM or more, 330 TPM or more, 340 TPM or more, 350 TPM or more, 360 TPM or more, 370 TPM or more, 380 TPM or more, 390 TPM or more, 400 TPM or more, 410 TPM or more, 420 TPM or more, 430 TPM or more, 440 TPM or more, 450 TPM or more, 460 TPM or more, 470 TPM or more, 480 TPM or more, 490 TPM or more, 500 TPM or more, 510 TPM or more, 520 TPM or more, 530 TPM or more, 540 TPM or more, 550 TPM or more, 560 TPM or more, 570 TPM or more, 580 TPM or more, 590 TPM or more, 600 TPM or more, 610 TPM or more, 620 TPM or more, 630 TPM or more, 640 TPM or more, 650 TPM or more, 660 TPM or more, 670 TPM or more, 680 TPM or more, 690 TPM or more, 700 TPM or more, 710 TPM or more, 720 TPM or more, 730 TPM or more, 740 TPM or more, 750 TPM or more, 760 TPM 390 TPM or above, 400 TPM or above, 410 TPM or above, 420 TPM or above, 430 TPM or above, 440 TPM or above, 450 TPM or above, 460 TPM or above, 470 TPM or above, 480 TPM or above, 490 TPM or above, 500 TPM or above, 510 TPM or above, 520 TPM or above, 530 TPM or above, 540 TPM or above, 550 TPM or above, 560 TPM or above, 570 TPM or above, 580 TPM or above or 590 TPM or above. Furthermore, the upper limit of the twist number can be, for example, 590 TPM or less, 580 TPM or less, 570 TPM or less, 560 TPM or less, 550 TPM or less, 540 TPM or less, 530 TPM or less, 520 TPM or less, 510 TPM or less, 500 TPM or less, 490 TPM or less, 480 TPM or less, 470 TPM or less, 460 TPM or less, 450 TPM or less, 440 TPM or less, 450 TPM or less, 460 TPM or less, 470 TPM or less, 480 TPM or less, 49 ... 30 TPM or less, 420 TPM or less, 410 TPM or less, 400 TPM or less, 390 TPM or less, 380 TPM or less, 370 TPM or less, 360 TPM or less, 350 TPM or less, 340 TPM or less, 330 TPM or less, 320 TPM or less, 310 TPM or less, 300 TPM or less, 290 TPM or less, 280 TPM or less, 270 TPM or less, or 260 TPM or less.

[0102] In an exemplary embodiment, the number of twists of the first pre-twisted yarn containing para-aramid fiber (first number of twists) and the number of twists of the second pre-twisted yarn containing different fibers (second number of twists) may be the same or different. In order to impart the twist number as described above, for example, a CC twisting machine (Cable Corder twisting machine) or a circular twisting machine may be used, wherein the number of twists of each pre-twisted yarn being the same means that when the device is used, the number of twists of each pre-twisted yarn is set to be the same. However, depending on the equipment or process conditions (for example, annealing in the drying stage after immersion in the binder solution), a difference in the number of twists within about 15%, within 10%, or within 5% of the set value may occur.

[0103] In an exemplary embodiment, the cord may be formed by secondarily twisting the first primary twist yarn and the second primary twist yarn in the range of 250 to 600 TPM. For example, when the first primary twist yarn and the second primary twist yarn are secondarily twisted together, the twist number (third twist number) may be 260 TPM or more, 270 TPM or more, 280 TPM or more, 290 TPM or more, 300 TPM or more, 310 TPM or more, 320 TPM or more, 330 TPM or more, 340 TPM or more, 350 TPM or more, 360 TPM or more, 370 TPM or more, 380 TPM or more, 390 TPM or more, 400 TPM or more , 410 TPM or above, 420 TPM or above, 430 TPM or above, 440 TPM or above, 450 TPM or above, 460 TPM or above, 470 TPM or above, 480 TPM or above, 490 TPM or above, 500 TPM or above, 510 TPM or above, 520 TPM or above, 530 TPM or above, 540 TPM or above, 550 TPM or above, 560 TPM or above, 570 TPM or above, 580 TPM or above or 590 TPM or above. And, its upper limit can be, for example, 590 TPM or less, 580 TPM or less, 570 TPM or less, 560 TPM or less, 550 TPM or less, 540 TPM or less, 530 TPM or less, 520 TPM or less, 510 TPM or less, 500 TPM or less, 490 TPM or less, 480 TPM or less, 470 TPM or less, 460 TPM or less, 450 TPM or less, 440 TPM or less, 430 TPM or less, 0TPM or less, 420TPM or less, 410TPM or less, 400TPM or less, 390TPM or less, 380TPM or less, 370TPM or less, 360TPM or less, 350TPM or less, 340TPM or less, 330TPM or less, 320TPM or less, 310TPM or less, 300TPM or less, 290TPM or less, 280TPM or less, 270TPM or less, or 260TPM or less.

[0104] In an exemplary embodiment, the twist count of the first and second pre-twisted yarns (i.e., the twist count of the primary twist) and the twist count of the secondary twist may be the same or different. In a specific embodiment of the present application, the twist count during the primary twist and the twist count during the secondary twist may be set to be the same. However, in some cases, in the final product, the twist count during the primary twist and the twist count during the secondary twist may be slightly different. Specifically, in the case of a CC twisting machine (Cab1eCorder twisting machine) for making cords, it is driven by a motor. The yarn in the creel passes through a disc connected to the motor and is connected to an adjuster (the part where the pre-twisted yarn and the pre-twisted yarn meet for secondary twisting). The yarn at the port passes through a tension adjustment guide roller and is connected to the adjuster. At this time, due to the rotation of the motor, the adjuster connected to the yarn coming out of the disc will also rotate. Due to this mechanical movement, primary twisting is applied to the creel portion yarn and the port portion yarn connected by the rotation of the motor. The pre-twisted yarn is twisted in the adjuster for secondary twisting. In this way, the raw cord is manufactured while twisting occurs due to the rotational motion of the motor. Even when the number of twists of the primary twist and the secondary twist are given (set) the same, the number of twists of the primary twist and the secondary twist may be slightly different due to the friction generated by the winding tension or the guide roller.

[0105] As described above, the cord of the present application includes a first primary twist yarn and a second primary twist yarn having a predetermined number of twists, and is formed by twisting the first primary twist yarn and the second primary twist yarn together. At this time, the filaments used to form the first primary twist yarn and the filaments used to form the second primary twist yarn are simultaneously primary twisted by a CC twisting machine (e.g., a cable corder twisting machine) or a circular twisting machine, thereby forming the first primary twist yarn and the second primary twist yarn. Therefore, the twist direction (first twist direction) of the first primary twist yarn and the twist direction (second twist direction) of the second primary twist yarn can be the same. And, when a CC twisting machine (e.g., a cable corder twisting machine) or a circular twisting machine is used, after the primary twisting, the secondary twisting can be continuously performed simultaneously with the primary twisting, wherein the twist direction (i.e., the third twist direction) of the secondary twisting can be opposite to the first twist direction (or the second twist direction).

[0106] In a specific embodiment of the present application, the content ratio of the first primary twisted yarn and the second primary twisted yarn can be appropriately adjusted to a level that can achieve the purpose of the present application. For example, based on the cord, specifically, the total weight of the first primary twisted yarn and the second primary twisted yarn contained in the raw cord is 100 weight%, the content of the first primary twisted yarn can be 10 weight% or more, 15 weight% or more, 20 weight% or more, 25 weight% or more, 30 weight% or more, 35 weight% or more, 40 weight% or more, 45 weight% or more, 50 weight% or more, 55 weight% or more, 60 weight% or more, 65 weight% or more, 70 weight% or more, 75 weight% or more, 80 weight% or more, 85 weight% or more, or 90 weight% or more. And, the upper limit thereof may be, for example, 90 wt% or less, 85 wt% or less, 80 wt% or less, 75 wt% or less, 70 wt% or less, 65 wt% or less, 60 wt% or less, 55 wt% or less, 50 wt% or less, 45 wt% or less, 40 wt% or less, 35 wt% or less, 30 wt% or less, 25 wt% or less, 20 wt% or less, 15 wt% or less, or 10 wt% or less. The content of the second pre-twisted yarn may be determined based on the content of the first pre-twisted yarn described above.

[0107] In an exemplary embodiment, the cord may be a two-ply or three-ply cord. For example, the cord may have a two-ply structure in which one first primary twisted yarn and one second primary twisted yarn are twisted together twice. Alternatively, the cord may have a three-ply structure in which two first primary twisted yarns having the above-mentioned fineness and one second primary twisted yarn having the above-mentioned fineness are twisted together twice.

[0108] According to a specific embodiment of the present application, when a first primarily twisted yarn (primarily twisted yarn comprising para-aramid fiber) and a second primarily twisted yarn (primarily twisted yarn comprising different fibers) form a plied yarn together, the length ratio of the first primarily twisted yarn to the second primarily twisted yarn (the length of the first primarily twisted yarn (L)) measured after the secondary twist is unwound is 1 ) / length of the second primary twisted yarn (L 2 )) can be in the range of 1.0 to 1.10 times relative to the plied yarn (raw cord or dipped cord).

[0109] The above length ratio (length of the first pre-twisted yarn (L 1 ) / length of the second primary twisted yarn (L 2)) makes the first primary twist yarn (primary twist yarn containing para-aramid fiber) with a higher modulus longer, thereby, in the early stage of the SS curve pattern representing the tensile performance of the cord, the physical properties of the second primary twist yarn (such as nylon) with a lower modulus are exhibited. This feature plays a role in reducing the unevenness of the tire shape during the tire manufacturing process. For example, in the case of a cap layer wound in the circumferential direction of the tire, when the initial modulus of the cord is high, it will resist the pressure of expansion during the tire molding process, and therefore, the function of the tread portion will not be properly expressed. Therefore, in tire manufacturing, it is more effective to exhibit low modulus characteristics in the early stage of the SS curve pattern of the cap layer cord. After the tire is manufactured, it must exhibit a high elastic modulus in order to prevent the belt layer cord from falling off during high-speed driving and maintain its ability to contact the ground. For this reason, it is more effective in terms of tire performance to exhibit a high elastic modulus after the elongation area consumed in tire manufacturing. Therefore, the cord manufactured by changing the length of the first primary twist yarn and the second primary twist yarn having different elastic moduli can be very effective in terms of tire manufacturing and performance.

[0110] If the length ratio of the first pre-twisted yarn to the second pre-twisted yarn (the length of the first pre-twisted yarn (L 1 ) / length of the second primary twisted yarn (L 2 )) is less than 1.0, the first primary twist yarn with a high modulus becomes short, and the physical properties of the aramid are preferentially degraded, which can have an adverse effect on tire manufacturing. In addition, the high initial modulus greatly reduces the fatigue performance under repeated tension and compression. If the length ratio of the first primary twist yarn to the second primary twist yarn (the length of the first primary twist yarn (L 1 ) / length of the second primary twisted yarn (L 2 )) exceeds 1.10, the first primary twisted yarn and the second primary twisted yarn receive separate forces under the cord tension, which will reduce the stiffness of the final cord.

[0111] Specifically, the lower limit of the length ratio may be, for example, 1.01 or more, 1.02 or more, 1.03 or more, 1.04 or more, or 1.05 or more, and the upper limit thereof may be, for example, 1.09 or less, 1.08 or less, 1.07 or less, 1.06 or less, or 1.05 or less.

[0112] In a specific example of the present application, the control of the length ratio as described above can be achieved by adjusting the respective tensions applied to the filaments forming the first primary twist yarn and the filaments forming the second primary twist yarn during the primary twisting and / or secondary twisting process for manufacturing the cord. For example, when the primary twisting and the secondary twisting are performed, the tension applied to the para-aramid fiber (forming the first primary twist yarn) is smaller than the tension applied to the different fibers forming the second primary twist yarn, thereby making the length of the first primary twist yarn longer than the length of the second primary twist yarn.

[0113] In an exemplary embodiment, the cord may further include a coating layer formed on the first primary twisted yarn and the second primary twisted yarn. That is, the cord may include: a raw cord; and a coating layer formed on the raw cord.

[0114] The coating layer refers to a layer formed by a coating liquid capable of exhibiting a predetermined function. Such a coating layer may be formed on at least a portion of the primary twisted yarn. There is no particular limitation on the method for forming the coating layer, and for example, the coating layer may be formed by a known dipping or spraying method.

[0115] The coating layer may be configured to impart predetermined properties to the cord or to improve the properties of the cord. For example, the coating layer may be a layer capable of imparting an adhesive function to the cord, but the properties imparted or improved by the coating layer are not limited to the adhesive function.

[0116] In an exemplary embodiment, the coating can be formed by an adhesive (composition). In a non-limiting example, the coating can include or be formed by a resorcinol formaldehyde latex (RFL) adhesive (composition), an epoxy resin adhesive (composition) or a polyurethane adhesive (composition). In another example, the coating can be formed by an adhesive that does not contain an RFL component. However, the adhesive components that form the coating are not limited to those described above.

[0117] Although not particularly limited, the adhesive composition may include an aqueous or non-aqueous solvent.Such an adhesive enables the fiber cord to exhibit improved adhesion to other adjacent components in tire reinforcement applications.

[0118] In an exemplary embodiment, the cord having a coating formed thereon, i.e., a dipped cord, may include a coating (or coating component) in a range of 1 to 10 wt % relative to its total weight (100 wt %, which is the total content including the fiber component and the coating component). For example, the upper limit of the coating content may be 9 wt % or less, 8 wt % or less, 7 wt % or less, 6 wt % or less, 5 wt % or less, 4 wt % or less, or 3 wt % or less, and the lower limit thereof may be 2 wt % or more, 3 wt % or more, 4 wt % or more, 5 wt % or more, 6 wt % or more, 7 wt % or more, 8 wt % or more, or 9 wt % or more.

[0119] In a specific embodiment of the present application, the first primary twist yarn of the cord may exhibit a predetermined crystallization property. Specifically, the coating may be formed by applying a predetermined tension and heat, similar to the manufacturing method described below, and during this treatment, the microstructure of the para-aramid fiber changes, just as the apparent crystal size of the para-aramid fiber becomes larger. As confirmed in the test described below, as the apparent crystal size of the para-aramid fiber becomes larger, the creep strain may become lower.

[0120] In an exemplary embodiment, the apparent crystal size of the para-aramid fiber contained in the dipped cord based on the 110 plane may be 7.2 nm or more, 7.3 nm or more, 7.4 nm or more, 7.5 nm or more, 7.6 nm or more, 7.7 nm or more, 7.8 nm or more, 7.9 nm or more, 8.0 nm or more, 8.1 nm or more, 8.2 nm or more, 8.3 nm or more, 8.4 nm or more, 8.5 nm or more, 8.6 nm or more, 8.7 nm or more, 8.8 nm or more, 8.9 nm or more, or 9.0 nm or more. And, the upper limit thereof may be, for example, 10.0 nm or less, 9.5 nm or less, or 9.0 nm or less. As described later, the apparent crystal size of the para-aramid fiber contained in the dipped cord based on the 110 plane may be measured relative to the inner portion to which the coating liquid is not applied after the aramid is separated from the dipped cord.

[0121] In an exemplary embodiment, the apparent crystal size of the para-aramid fiber contained in the dipped cord based on 200 plane may be 5.5 nm or more, 5.6 nm or more, 5.7 nm or more, 5.8 nm or more, 5.9 nm or more, 6.0 nm or more, 6.2 nm or more, 6.3 nm or more, or 6.4 nm or more, and 6.5 nm or less, 6.4 nm or less, 6.3 nm or less, 6.2 nm or less, 6.1 nm or less, or 6.0 nm or less. As described later, the apparent crystal size of the para-aramid fiber contained in the dipped cord based on 200 plane may be measured relative to the inner portion to which the coating liquid is not applied after separating the aramid from the dipped cord.

[0122] In an exemplary embodiment, the crystallinity of the para-aramid fiber contained in the dipped cord may be 72% or more, 72.5% or more, 73.0% or more, 73.5% or more, 74.0% or more, 74.5% or more, 75.0% or more, 75.5% or more, 76.0% or more, 76.5% or more, 77.0% or more, 77.5% or more, 78.0% or more, 78.5% or more, 79.0% or more, or 79.5% or more, and the upper limit thereof may be, for example, 80% or less, 79.5% or less, 79.0% or less, 78.5% or less, 78.0% or less, 77.5% or less, 77.0% or less, 76.5% or less, 76.0% or less, 75.5% or less, 75% or less, 74.5% or less, 74.0% or less, 73.5% or less, 73% or less, or 72.5% or less. As described later, the crystallinity of the para-aramid fiber contained in the dipped cord can be measured with respect to the inner portion to which the coating liquid is not applied after the aramid fiber is separated from the dipped cord.

[0123] As described above, in the present application, the raw cord is manufactured using para-aramid fiber having a relatively large crystal size and crystallinity, and the coating is formed by heat treating and tensioning the raw cord, so that the para-aramid fiber contained in the dipped cord also shows a larger value. As a result, as confirmed by the creep strain described below, the deformation degree of the fiber and the cord can be improved.

[0124] In a specific embodiment of the present application, the cord having the above-mentioned configuration may exhibit the following characteristics.

[0125] In an exemplary embodiment, the creep strain (%) of the cord may be 3.0% or less. Specifically, the cord may satisfy a creep strain (%) of 2.9% or less, 2.85% or less, 2.8% or less, 2.75% or less, 2.7% or less, 2.65% or less, 2.6% or less, 2.55% or less, 2.5% or less, 2.45% or less, 2.4% or less, 2.35% or less, 2.3% or less, 2.25% or less, or 2.20% or less. Although not particularly limited, the lower limit of the creep strain (%) may be, for example, 1.5% or more or 2.0% or more. Creep strain refers to the deformation of a material according to a constant load and temperature, which is different from the meaning of elongation, which is the measurement of deformation until the material breaks or cuts as the load continues to increase. In the case of elongation, it measures how long the material can be stretched, and is usually converted to a numerical value of the length stretched until the material breaks or cuts. On the other hand, creep strain represents the strain under a fixed load. Therefore, high creep strain means that the shape of the product is greatly deformed under constant load. Therefore, if a cord with high creep strain is used, there is a higher possibility that the tire shape will be deformed due to long-term parking.

[0126] As described later, according to ASTM D2990, creep strain (%) is measured by applying a load (tension) of 0.8 g / d (wherein d is denier and g is a unit of weight) to the cord at 80°C for 24 hours, which may refer to the length change rate of the cord confirmed under the above conditions (strain in the load direction). According to a specific embodiment of the present application, before measuring the creep strain, the cord may be subjected to a predetermined pretreatment. For example, the creep strain of the cord may be measured after the following pretreatment, wherein the cord is stored under constant temperature and humidity conditions (control conditions are 20±2°C, humidity: 65±5%) for 24 hours, and a load (tension) of 0.01 g / d (wherein d is denier and g is a unit of silver weight) is applied to the cord at 180°C for 15 minutes.

[0127] In an exemplary embodiment, the stiffness of the cord can be more than 24.0kgf. Specifically, the stiffness of the cord can be, for example, more than 24.5kgf, more than 25.0kgf, more than 25.5kgf, more than 26.0kgf, more than 26.5kgf, more than 27.0kgf, more than 27.5kgf, more than 28.0kgf, more than 28.5kgf, more than 29.0kgf, more than 29.5kgf or more than 30.0kgf. And, there is no particular restriction on its upper limit, but it can be, for example, less than 40kgf, less than 35kgf or less than 30kgf. As described below, the stiffness of the cord can be measured according to ASTM D885. At this time, the cord can be a dipped cord.

[0128] In an exemplary embodiment, the toughness of the cord may be greater than 13.0 g / d. Specifically, the toughness of the cord may be, for example, 13.5 g / d or more, 14.0 g / d or more, 14.5 g / d or more, 15.0 g / d or more, 15.5 g / d or more, 16.0 g / d or more, 16.5 g / d or more, 17.0 g / d or more, 18.0 g / d or more, 18.5 g / d or more, 19.0 g / d or more, or 19.5 g / d or more. Also, there is no particular limit to its upper limit, but it may be, for example, 25 g / d or less or 20 g / d or less. As described below, the toughness of the cord may be measured according to ASTM D885. At this time, the cord may be a dipped cord.

[0129] In an exemplary embodiment, the elongation (elongation at break) of the cord may be 7.0% or more. Specifically, the elongation of the cord may be, for example, 7.5% or more, 8.0% or more, 8.5% or more, 9.0% or more, 9.5% or more, or 10% or more. Also, there is no particular limitation on its upper limit, but it may be, for example, 15% or less. As described below, the elongation of the cord may be measured according to ASTM D885. At this time, the cord may be a dipped cord.

[0130] In another example of the present application, the present application relates to a method for manufacturing the above-mentioned cord. The above-mentioned cord can be manufactured by the above-mentioned manufacturing method. Therefore, in the description of the characteristics of the above-mentioned cord, the description of the overlapping configuration or characteristics will be omitted from the description of the manufacturing method described later.

[0131] In a specific example of the present application, a method for manufacturing a cord may include the following steps: preparing a para-aramid fiber having a crystallinity of 67% or more, an apparent crystal size of 5.8 to 7.0 nm based on a 110 plane, a total fineness of 200 to 1600 deniers, and a tenacity of 22 g / d or more; and secondarily twisting a first primary twist yarn and a second primary twist yarn together to prepare a cord as a plied yarn, wherein the first primary twist yarn is formed by imparting twist to the para-aramid fiber, and wherein the second primary twist yarn is formed by imparting twist to a different fiber different from the para-aramid fiber.

[0132] In the above method, the first pre-twisted yarn may be manufactured by imparting a twist of 250 to 600 TPM to the para-aramid fiber. The specific twist number of the first pre-twisted yarn is the same as described above.

[0133] In the above method, the second primary twisted yarn may be manufactured by imparting a twist of 250 to 600 TPM to the different fibers. The specific twist number of the second primary twisted yarn is the same as described above.

[0134] In the above method, the first primary twisted yarn and the second primary twisted yarn may be twisted at a twist number of 250 to 600 TPM to form a cord. The specific twist number during the secondary twisting process is the same as described above.

[0135] In an exemplary embodiment, the method may further include forming a coating on the plied yarn (raw cord). At this time, "forming a coating" may refer to applying a coating forming composition (coating solution) to the raw cord. The applied coating forming composition may be heat treated, such as drying or curing, which will be described later. In this case, the coating may refer to a layer obtained by heat treatment.

[0136] There is no particular limitation on the method of applying the coating-forming composition (coating liquid) to the raw cord, and a dipping or spraying method may be used.

[0137] For example, the method may include spraying the coating-forming composition (coating liquid) onto the plied yarn (raw cord). That is, the above method may form a coating layer by spraying the coating-forming composition (coating liquid) onto the plied yarn.

[0138] In another exemplary embodiment, the method may include dipping the plied yarn (raw cord) in a coating-forming composition (coating solution). That is, the above method may form a coating by dipping the plied yarn in a coating-forming composition (coating solution). When the plied yarn is immersed in a coating-forming composition (coating solution), there is no particular restriction on the specific method of dipping the plied yarn in the coating-forming composition. For example, the following method may be used, wherein the plied yarn or a fiber substrate containing it is immersed in a coating bath filled with a coating-forming composition while being conveyed using a roller. The cord coated with the coating-forming composition after dipping may be referred to as an impregnated cord.

[0139] In an exemplary embodiment, the formation of the coating may be performed while undergoing the conveying of the cord, the coating-forming composition being applied (sprayed or dipped) onto the cord, and / or subsequent heat treatment. For example, the step (process) of forming the coating may include one or more of the conveying, dipping (or spraying), and heat treatment of the cord. Specifically, the step (process) of forming the coating may include: heat treatment while applying a predetermined amount of tension to the plied yarn coated with the coating-forming composition; while applying a predetermined amount of tension, applying the coating-forming composition to the plied yarn and heat treating; or conveying the plied yarn, applying the coating-forming composition, and heat treating while applying a predetermined amount of tension.

[0140] In a specific embodiment of the present application, the heat treatment may be performed within a predetermined temperature range. For example, the heat treatment may be performed at a temperature above 50° C., specifically within a range of 60 to 350° C. Although not particularly limited, the heat treatment may be performed for 10 to 300 seconds.

[0141] In an exemplary embodiment, the method may include two or more heat treatment steps. Specifically, the method may include a first heat treatment step performed at a temperature of 70 to 180° C.; and a second heat treatment step performed at a temperature of 200 to 250° C. There is no particular limitation on the time for which the heat treatment is performed, but, for example, each of such heat treatments may be performed for about 30 to 300 seconds.

[0142] In an exemplary embodiment, the temperature at which the first heat treatment is performed may be lower than the temperature at which the second heat treatment is performed. Specifically, the first heat treatment temperature may be in the range of 70 to 180° C., and the second heat treatment temperature may be in the range of 200 to 250° C. At this time, the first heat treatment performed at a relatively low temperature may be referred to as a drying process, and the second heat treatment performed at a relatively high temperature may be referred to as a curing process.

[0143] In an exemplary embodiment, the formation of the coating layer may be performed while applying tension to the plied yarn (green cord).

[0144] For example, the tension applied to the plied yarn may be 0.1 kg / cord or more, 0.2 kg / cord or more, 0.3 kg / cord or more, 0.4 kg / cord or more, 0.5 kg / cord or more, 0.6 kg / cord or more, 0.7 kg / cord or more, 0.8 kg / cord or more, or 0.9 kg / cord or more. And, the upper limit thereof may be, for example, 1.5 kg / cord or less, 1.4 kg / cord or less, 1.3 kg / cord or less, 1.2 kg / cord or less, 1.1 kg / cord or less, 1.0 kg / cord or less, 0.9 kg / cord or less, 0.8 kg / cord or less, 0.7 kg / cord or less, 0.6 kg / cord or less, 0.5 kg / cord or less, 0.4 kg / cord or less, 0.3 kg / cord or less, or 0.2 kg / cord or less.

[0145] In an exemplary embodiment, when the step (process) of forming a coating is performed while applying tension, the step (process) of forming a coating can be used in the sense of including: heat-treating the plied yarn coated with the coating-forming composition while applying the tension of the above magnitude to the plied yarn. More specifically, the step (process) of forming a coating performed while applying tension can be used in the sense of including the following process: after applying the coating-forming composition, a second heat treatment is performed while applying the tension of the above magnitude to the plied yarn that has been subjected to the first heat treatment. Since the heat treatment applying a high temperature, especially the second heat treatment, greatly affects the final physical properties of the cord, it is very important to satisfy the above tension range. Therefore, at least during the heat treatment process, more specifically during the second heat treatment process, the tension within the above range can be maintained. In addition, the transfer and dipping (spraying) for forming the coating and the first heat treatment process can be the same or different (slightly changed).

[0146] When heat and tension are applied as described above, the tension causes the molecular chains to become more oriented in the direction of the fiber axis, and this orientation is determined by the heat, and therefore, the microstructure may change. Since heat and / or tension are applied during the impregnation process, the microstructure of the para-aramid fiber in the impregnated cord has a larger crystal size than the yarn state. As described above, in the present application, a para-aramid yarn with a higher crystallinity is used, and further, due to the impregnation treatment, the crystallinity of the para-aramid fiber of the impregnated cord is increased, thereby reducing the degree of deformation against external forces (i.e., the deformation resistance is improved). This is confirmed by the above-mentioned creep strain (%).

[0147] In an exemplary embodiment, dipping or spraying may be performed one or more times. If dipping or spraying is performed two or more times, the components of the coating-forming composition used for each dipping or spraying may be the same or different.

[0148] For example, the first dipping, the second dipping and the heat treatment may be performed sequentially. At this time, the heat treatment may sequentially include the first heat treatment (eg, drying) and / or the second heat treatment (eg, curing).

[0149] In another exemplary embodiment, the first dipping, the heat treatment, the second dipping, and the heat treatment may be performed sequentially. In this case, the heat treatment performed between the first dipping and the second dipping may be a drying process performed at a relatively low temperature, and the heat treatment performed after the second dipping may be a curing process performed at a relatively high temperature.

[0150] In an exemplary embodiment, the method may be a method in which para-aramid fibers (filaments) are primarily twisted in a first twist direction to produce a first primarily twisted yarn, and simultaneously, different fibers (filaments) are primarily twisted in a second twist direction to produce a second primarily twisted yarn.

[0151] In an exemplary embodiment, the method may be a method of producing a plied yarn by secondarily twisting the first primary twist yarn and the second primary twist yarn in a third twist direction after or simultaneously with producing the primary twist yarn as described above. In this case, the first twist direction and the second twist direction may be the same, and the first twist direction and the third twist direction may be different from each other.

[0152] According to a specific embodiment of the present application, when producing ply-twisted yarn, a twisting machine such as a cable corder that performs primary twisting and secondary twisting at the same time can be used. For example, in the case of manufacturing a hybrid cord, since the first primary twisted yarn forms filaments (para-aramid filament yarn) and the second primary twisted yarn forms filaments (e.g., nylon, polyester, etc.) are respectively secondary twisted by a twisting machine (e.g., cable corder) at the same time, and the first primary twisted yarn and the second primary twisted yarn are also formed, the twist direction (first twist direction) of the first primary twisted yarn can be the same as the twist direction (second twist direction) of the second primary twisted yarn. In addition, according to a specific embodiment of the present application, it is carried out using a twisting machine (such as a cable corder) that can perform primary twisting and secondary twisting at the same time, and after the primary twisting, the secondary twisting can be continuously performed at the same time as the primary twisting. The twist direction of the secondary twisting (i.e., the third twist direction) can be opposite to the first twist direction (or the second twist direction).

[0153] In an exemplary embodiment, the method may be a method of forming a pre-twisted yarn by imparting a twist number in the range of 250 to 600 TPM to the fiber (filament) forming the pre-twisted yarn. That is, the twist number imparted to the first pre-twisted yarn and the second pre-twisted yarn is in the range of 250 to 600 TPM.

[0154] In an exemplary embodiment, the method may include secondarily twisting the first primary twist yarn and the second primary twist yarn within a twist number range of 250 to 600 TPM to form a ply-twisted yarn.

[0155] In a specific embodiment of the present application, the method may be a method of controlling the tension applied to the aromatic polyamide fiber (forming the first primary twist yarn) to be smaller than the tension applied to the different fiber (forming the second primary twist yarn) during the primary twisting and / or the secondary twisting. In this way, the length ratio of the first primary twist yarn to the second primary twist yarn measured after the secondary twisting is unwound (the length of the first primary twist yarn (L 1 ) / length of the second primary twisted yarn (L 2 )) can be adjusted in the range of 1.0 to 1.10 times relative to the ply-twisted yarn (raw cord or dipped cord).

[0156] Regarding the manufacturing method of the present application, descriptions on the configuration, characteristics, and manufacturing of the cords and the primary twisted yarns forming the cords other than the above descriptions are the same as those described above and thus will be omitted.

[0157] In a specific embodiment of the present application, the method for manufacturing a cord may further include a method for producing (preparing) the above-mentioned para-aramid fiber. For example, the para-aramid fiber can be produced by the above-mentioned method, and the method for manufacturing a cord may further include: a step of filtering the reaction raw materials to remove impurities; a step of adding an aromatic diamine to a mixed solvent containing an organic solvent and an inorganic salt to form a slurry; a step of adding an aromatic diacid halide to a reactor containing the slurry three or more times, and reacting the mixture to form a para-aramid polymer; and a step of spinning a spinning solution containing a para-aramid polymer to produce fibers. At this time, in the step of forming the polymer, during the first addition and the second addition of the aromatic diacid halide, the difference between the cooling water temperature on the cooling water inlet side and the cooling water outlet side for cooling the reactor can be controlled within 50°C.

[0158] Since the specific process of manufacturing the para-aramid fiber is the same as described above, the description thereof is omitted.

[0159] In another example related to the present application, the present application relates to a rubber composite material or a rubber reinforced material comprising the cord. In addition to the cord, the rubber composite material or the rubber reinforced material may further include a rubber substrate, such as a rubber sheet.

[0160] In another example of the present application, the present application relates to a tire comprising the cord. The tire may have a known configuration, such as a tread, a shoulder, a sidewall, a cap layer, a belt layer, a carcass (or a carcass cord), an inner liner, a bead, and the like.

[0161] Beneficial Effects

[0162] According to the present application, a cord is provided, which includes para-aramid fiber having a large crystal size and high crystallinity as a primary twist yarn component, thereby exhibiting excellent mechanical properties (such as tensile properties). The cord has high resistance to external force deformation and can be used as a tire reinforcement material. DETAILED DESCRIPTION

[0163] Hereinafter, the functions and effects of the present invention will be described in more detail with reference to specific embodiments of the present disclosure. However, these embodiments are only for illustrative purposes and are not intended to limit the scope of rights of the present invention in any sense.

[0164] Test Example 1: Evaluation of para-aramid polymer and fiber

[0165] 1. Preparation of para-aramid polymers and evaluation of their physical properties

[0166] The physical properties of the para-aramid polymers obtained in the following Synthesis Examples were measured according to the following methods.

[0167] (1) Measurement of intrinsic viscosity

[0168] The intrinsic viscosity of the polymer is measured according to Equation 1 below.

[0169] [Equation 1]

[0170] IV=ln(η rel ) / C

[0171] In equation 1, ln is a natural logarithmic function, C is the concentration of a polymer solution (a solution in which 0.5 g of a polymer is dissolved in 100 mL of 98 wt % concentrated sulfuric acid), and the relative viscosity (ηre l ) is the ratio of the flow time between the polymer solution and the solvent measured by a capillary viscometer at 30°C.

[0172] (2) Measurement of intrinsic viscosity deviation

[0173] Using standard sieves having mesh sizes of 1 mm and 2 mm, respectively, the washed and dried polymer was classified into a group of 2 mm or more, a group of 1 mm or more and less than 2 mm, and a group of less than 1 mm.

[0174] Then, the intrinsic viscosity of each group was measured, and then the difference between the maximum and minimum values ​​of the average intrinsic viscosity of the three groups was calculated to obtain the intrinsic viscosity deviation of the polymer.

[0175] (3) Content of inorganic impurities

[0176] The content of inorganic impurities in the para-aramid polymer was measured by the following method: 1 g of a sample was completely decomposed by acid treatment, and then the concentration of ionized and residual inorganic impurities in the sample was measured using an inductively coupled plasma spectrophotometer.

[0177] Synthesis Example 1: Preparation of para-aramid polymer (PPTA-1)

[0178] As the reaction raw materials, N-methyl-2-pyrrolidone (NMP), CaCl 2 , p-phenylenediamine (PPD) and terephthaloyl chloride (TPC) were passed through a filter with a diameter of 0.1 μm to remove impurities in the reaction raw materials.

[0179] NMP as an organic solvent and CaCl as an inorganic salt 2 A mixed solvent mixed at a weight ratio of 92:8 was added to a reactor under a nitrogen atmosphere, and PPD was added thereto so that the concentration of PPD in the slurry was 5 wt %, to prepare a slurry.

[0180] Then, 30 mol% of TPC corresponding to the mole number of PPD was added to the reactor cooled to 30° C., and then reacted for 10 minutes. At this time, the stirring speed of the reactor was adjusted to about 200 rpm so that the cooling water temperature difference between the cooling water inlet and the cooling water outlet was controlled to be 20° C.

[0181] Subsequently, 60 mol% of TPC corresponding to the mole number of PPD was added to the reactor cooled to 30°C and then reacted for 30 minutes. At this time, the stirring speed of the reactor was adjusted to about 200 rpm so that the temperature difference between the cooling water inlet and the cooling water outlet was controlled to about 20°C.

[0182] Finally, 10 mol % of TPC corresponding to the mole number of PPD was added to the reactor cooled to 30° C., and then reacted for 30 minutes to prepare a para-aramid polymer.

[0183] Water and NaOH were added to the solution containing the para-aramid polymer to neutralize the acid, and then, after the para-aramid polymer was pulverized, the polymerization solvent contained in the para-aramid polymer was extracted with water, followed by dehydration and drying to finally obtain PPTA-1.

[0184] The intrinsic viscosity of the PPTA-1 thus prepared was 5.4 dl / g, and the content of inorganic impurities in the polymer was 48 ppb. In addition, using standard sieves having mesh sizes of 1 mm and 2 mm, they were divided into a group of 2 mm or more, a group of 1 mm or more and less than 2 mm, and a group of less than 1 mm, and the intrinsic viscosity of each group was measured. Then, the intrinsic viscosity deviation calculated as the difference between the maximum and minimum values ​​of the average intrinsic viscosity was 0.85 dl / g.

[0185] Synthesis Example 2: Preparation of para-aramid polymer (PPTA-2)

[0186] NMP as an organic solvent and CaCl as an inorganic salt 2 A mixed solvent mixed in a weight ratio of 86:14 was added to a reactor under a nitrogen atmosphere, and PPD was added thereto so that the concentration of PPD in the slurry was 3 wt %, to prepare a slurry.

[0187] Then, 30 mol % of TPC corresponding to the mole number of PPD was added to the reactor cooled to 0° C., and then reacted at 5° C. for 30 minutes.

[0188] After 30 minutes, the difference between the cooling water temperature on the cooling water inlet side and the temperature on the cooling water outlet side was 65° C., and 60 mol % of TPC corresponding to the mol number of PPD was added to the reactor, followed by a reaction at 5° C. for 20 minutes. 10 mol % of TPC corresponding to the mol number of PPD was added to the reactor, followed by a reaction at 5° C. for 5 minutes to prepare a para-aramid polymer.

[0189] Water and NaOH were added to the solution containing the para-aramid polymer to neutralize the acid, and then, after the para-aramid polymer was pulverized, the polymerization solvent contained in the para-aramid polymer was extracted with water, followed by dehydration and drying to finally obtain PPTA-2.

[0190] The intrinsic viscosity of the PPTA-2 thus prepared was 5.4 dl / g, and the content of inorganic impurities in the polymer was 3150 ppb. In addition, using standard sieves with mesh sizes of 1 mm and 2 mm, they were divided into a group of 2 mm or more, a group of 1 mm or more and less than 2 mm, and a group of less than 1 mm, and the intrinsic viscosity of each group was measured. Then, the intrinsic viscosity deviation calculated as the difference between the maximum and minimum values ​​of the average intrinsic viscosity was 1.3 dl / g.

[0191] 2. Manufacture of para-aramid fiber and evaluation of physical properties

[0192] The physical properties of the para-aramid fibers obtained in the following Preparation Examples and Comparative Preparation Examples were measured according to the methods described below, and the results are shown in Table 1 below.

[0193] (1) Fineness (denier, denier)

[0194] The fineness is the denier (denier) expressed as the weight (g) of 9000 meters of yarn, which is measured according to ASTM D 1577.

[0195] (2) Tensile properties

[0196] The para-aramid fibers prepared in the Preparation Examples and Comparative Preparation Examples were cut into a length of 250 mm to prepare samples twisted at a TM (twist multiplier) of 1.1, and the samples were stored at a relative humidity of 55% and a temperature of 23° C. for 14 hours.

[0197] Then, according to the ASTM D885 standard test method, the sample was mounted on an INSTRON tester (Instron Engineering Corp, Canton, Mass), one side of the fiber was fixed, and the initial load was set to 1 / 30 g of the fineness (fineness × 1 / 30 g), and then the other side was stretched at a speed of 25 mm / min, and the tensile load (g) and elongation (strain) when the fiber was broken were measured. The tenacity (g / d) was obtained by dividing the measured tensile load by the fineness, and the Young's modulus was obtained by the slope of the stress-strain curve of the para-aramid fiber obtained under the above tensile load measurement conditions.

[0198] (3) X-ray diffraction (XRD) analysis

[0199] The microstructures of the para-aramid fibers prepared in the Preparation Examples and Comparative Preparation Examples were analyzed by X-ray diffraction patterns.

[0200] The para-aramid fibers prepared in the examples and comparative examples were cut into lengths of 20 to 30 mm, aligned as much as possible, and then attached to a support to prepare a sample. The prepared sample was suspended on a sample attachment, and the β-position was set to 0°. After preheating, the voltage and current of the XRD measuring device were gradually increased to the measuring conditions of 50 kV and 180 mA, and the equatorial pattern was measured. In addition, the main measuring conditions were set as follows.

[0201] Goniometer, continuous scan mode, scan angle range: 10° to 40°, scan speed: 2.

[0202] The 2θ positions of two peaks appearing between 20° and 21° and 22° and 23° in the scan profile were measured. The measured profile was processed using a multi-peak separation method program.

[0203] After linear distribution of the background from 15° to 35° at 2θ, two crystal peaks were separated to obtain the X-ray diffraction pattern.

[0204] i) Apparent crystal size (ACS)

[0205] Using the X-ray diffraction pattern and factors [2θ position, full width at half maximum (FWHM) of intensity], the apparent crystal size (ACS) is obtained by the Scherrer equation when K of each crystal plane is 1. Here, the apparent crystal size (ACS) refers to the average size of the corresponding crystal plane.

[0206] ii) Crystallinity (Xc)

[0207] Using the X-ray diffraction pattern, the crystallinity is obtained by the ratio between the crystalline peak and the amorphous peak.

[0208] iii) Orientation angle (OA)

[0209] After azimuth scanning at the position on each side of the X-ray diffraction pattern, the full width at half maximum (FWHM) of each peak was determined to obtain the orientation angle.

[0210] iv) Subcrystalline parameters (g II )

[0211] The para-aramid fibers prepared in the preparation examples and the comparative preparation examples were cut into lengths of 20 mm to 30 mm, aligned as much as possible, and then attached to a support to prepare a sample. The prepared sample was suspended on a sample attachment, and the β-position was set to 0 °. After preheating, the voltage and current of the XRD measuring device were gradually increased to the measurement conditions of 50 kV and 180 mA, and the meridional pattern was measured. In addition, the main measurement conditions were set as follows.

[0212] Goniometer, continuous scan mode, scan angle range: 10° to 40°, scan speed: 0.5 [the step / scan time provides enough beam exposure time to obtain 2,000 CPS, as the intensity of the peak is not significant].

[0213] The 2θ position of the peak (002 plane) appearing between 10° and 15° in the scan profile was measured. The secondary crystal parameters were derived by substituting the measured profile into the HOSEMANN equation of Equation 2 below.

[0214] [Equation 2]

[0215]

[0216] In Equation 2, δs is the dispersion of the diffraction peak, L is the apparent crystal size, d is the spacing of the lattice planes, and m is the order of the diffraction peak.

[0217] Preparation Example 1: Preparation of para-aramid fiber

[0218] The spinning solution was prepared by dissolving PPTA-1 obtained in Synthesis Example 1 in 99.8 wt % of sulfuric acid in an amount of 19 wt % based on the total weight of the spinning solution.

[0219] The spinning solution was spun through a spinneret having 133 holes at a speed of 650 m / min, and coagulated in a coagulation tank through an air gap to prepare filaments.

[0220] The coagulated filaments were washed with water to remove sulfuric acid and the like remaining on the filaments, dried, and then wound to obtain para-aramid fibers having a single filament fineness of 1.47 deniers and a total fineness of 213 deniers.

[0221] Preparation Example 2: Preparation of para-aramid fiber

[0222] The spinning solution was prepared by dissolving PPTA-1 obtained in Synthesis Example 1 in 99.8 wt % of sulfuric acid in an amount of 19 wt % based on the total weight of the spinning solution.

[0223] The spinning solution was spun through a spinneret having 665 holes at a speed of 620 m / min, and coagulated in a coagulation tank through an air gap to prepare filaments.

[0224] The coagulated filaments were washed with water to remove sulfuric acid and the like remaining on the filaments, dried, and then wound to obtain para-aramid fibers having a single filament fineness of 1.43 deniers and a total fineness of 988 deniers.

[0225] Preparation Example 3: Preparation of para-aramid fiber

[0226] The spinning solution was prepared by dissolving PPTA-1 obtained in Synthesis Example 1 in 99.8 wt % of sulfuric acid in an amount of 20 wt % based on the total weight of the spinning solution.

[0227] The spinning solution was spun through a spinneret having 665 holes at a speed of 600 m / min, and coagulated in a coagulation tank through an air gap to prepare filaments.

[0228] The coagulated filaments were washed with water to remove sulfuric acid and the like remaining on the filaments, dried, and then wound to obtain para-aramid fibers having a single filament fineness of 1.50 deniers and a total fineness of 1022 deniers.

[0229] Preparation Example 4: Preparation of para-aramid fiber

[0230] The spinning solution was prepared by dissolving PPTA-1 obtained in Synthesis Example 1 in 99.8 wt % of sulfuric acid in an amount of 19 wt % based on the total weight of the spinning solution.

[0231] The spinning solution was spun through a spinneret having 1000 holes at a speed of 650 m / min, and coagulated in a coagulation tank through an air gap to prepare filaments.

[0232] The coagulated filaments were washed with water to remove sulfuric acid and the like remaining on the filaments, dried, and then wound to obtain para-aramid fibers having a single filament fineness of 1.54 deniers and a total fineness of 1550 deniers.

[0233] Comparative Preparation Example 1: Preparation of para-aramid fiber

[0234] The spinning solution was prepared by dissolving PPTA-2 obtained in Synthesis Example 2 in 99.8 wt % of sulfuric acid in an amount of 19 wt % based on the total weight of the spinning solution.

[0235] The spinning solution was spun through a spinneret having 1000 holes at a speed of 600 m / min, and coagulated in a coagulation tank through an air gap to prepare filaments.

[0236] The coagulated filaments were washed with water to remove sulfuric acid and the like remaining on the filaments, dried, and then wound to obtain para-aramid fibers having a single filament fineness of 1.49 deniers and a total fineness of 1527 deniers.

[0237] For reference, when the spinning speed of the PPTA-2 obtained in Synthesis Example 2 was set to the same as that in Preparation Example 4, various physical properties were poor, and therefore, a para-aramid fiber having the same level of fineness as that of Preparation Example 4 was prepared, but the spinning speed was adjusted to the optimal speed of the PPTA-2 obtained in Synthesis Example 2.

[0238] [Table 1]

[0239]

[0240] * The apparent crystal size in Table 1 refers to the apparent crystal size based on the 110 plane and the apparent crystal size based on the 200 plane, and the orientation angle refers to the orientation angle based on the 110 plane and the orientation angle based on the 200 plane.

[0241] Referring to Table 1, it can be confirmed that the para-aramid fiber according to one embodiment is formed of a para-aramid polymer prepared by using a reaction raw material from which impurities are removed by controlling the addition conditions and the addition method of the reaction raw material, thereby providing various grades of high-quality para-aramid fibers.

[0242] Specifically, by comparing Preparation Examples 1, 2 and 4, which provide standard toughness aromatic polyamide fibers having a toughness of about 20 to 24 g / d, with Comparative Preparation Example 1, it can be confirmed that Preparation Examples 1, 2 and 4 exhibit larger crystal sizes, higher crystallinity and higher orientation, and further exhibit more excellent Young's modulus, compared with Comparative Preparation Example 1.

[0243] In addition, Preparation Example 3, which provides high-tenacity aramid fibers having a tenacity of 25 g / d or more, also exhibits a large crystal size, high crystallinity, and high orientation, confirming excellent tensile properties.

[0244] Test Example 2: Production of cord and evaluation of physical properties

[0245] Para-aramid filament yarns were produced by the same process as the preparation examples and comparative preparation examples described in Test Example 1, provided that the total fineness was controlled at a similar level of 1000 (±50 or less) denier. Each of the produced para-aramid filament yarns and 840 denier nylon filament yarns was put into a twisting machine (Cable Corder, Allma), and primary twisting in the Z direction and secondary twisting in the S direction were performed simultaneously, respectively, to prepare a 2-ply cable (raw cord). At this time, for the primary twisting and the secondary twisting, the Cable Corder was set to a twist number of 360 TPM (twists per meter), and the tension applied to each of the nylon filament yarn and the para-aramid filament yarn was adjusted so that the ratio of the length of the para-aramid single yarn (primarily twisted yarn) to the length of the nylon single yarn (primarily twisted yarn) in the plied yarn (raw cord) (=para-aramid single yarn length (L A ) / Nylon single yarn length (L N )) is set to 1.01. At this time, in order to determine the length ratio of the para-aramid single yarn and the nylon single yarn, a load of 0.05 g / d is applied to a 1 m long plied yarn (raw cord) sample to loosen the plied yarn, the para-aramid single yarn and the nylon single yarn are separated from each other, and then the length of the para-aramid single yarn and the length of the nylon single yarn are measured respectively under a load of 0.05 g / d. The raw cord prepared as described above contains about 40 to 50% by weight of the first primary twisted yarn (including the para-aramid single yarn) and about 50 to 60% by weight of the second primary twisted yarn (including the nylon fiber).

[0246] Then, the plied yarn (raw cord) is immersed in a resorcinol-formaldehyde-latex (RFL) adhesive solution containing 2.0 wt% of resorcinol, 3.2 wt% of formalin (37%), 1.1 wt% of sodium hydroxide (10%), 43.9 wt% of styrene / butadiene / vinyl pyridine (15 / 70 / 15) rubber (41%) and water. The plied yarn (raw cord) impregnated with the RFL solution is dried at 150°C for 100 seconds and heat-treated (cured) at 240°C for 100 seconds to complete the dipped cord. The tension applied to the plied twisted yarn during the dipping, drying and heat treatment process is 0.6 kg / cord. At this time, the content of the applied adhesive is about 4.5 to 5.0 wt% based on the total weight of the produced dipped cord 100 wt%.

[0247] The dipped cords produced as described above were measured for the following items of properties, and the results are shown in Table 2 below.

[0248] (1) Apparent crystal size and crystallinity of the para-aramid primary twisted yarn contained in the dipped cord based on the 110 plane and the 200 plane

[0249] The para-aramid ply twisted yarn was separated from the dipped cord, and the crystal properties of the para-aramid ply twisted yarn were measured in the same manner as in the measurement of the yarn microstructure described in Test Example 1 with respect to the inner portion to which the coating liquid was not applied.

[0250] (2) Creep strain of dipped cord (%)

[0251] According to ASTM D885, the dipped cord sample was placed under constant temperature and humidity conditions (according to ASTM D885, the conditions were controlled to be temperature: 20±2°C, humidity: 65±5%) for 24 hours, and then the cord was pretreated (dried) at a temperature of 180°C and a load of 0.01 g / d for 15 minutes. Since different fiber components (e.g., nylon) may be deformed by moisture, the same pretreatment as above was performed so that the creep strain (%) can be measured reproducibly.

[0252] After the above process, the hybrid dipped cord was subjected to creep evaluation using the method according to ASTM D2990, and the creep strain (%) was measured over time. Specifically, after a load of 0.8 g / d was applied to the cord at 80°C for 24 hours, the strain rate (deformation rate) in the direction (longitudinal direction) in which the load was applied was measured. (Creep strain (%) after 24 hours).

[0253] (3) Stiffness (kgf), toughness (breaking strength) (g / d) and elongation (breaking elongation) (%) of dipped cord

[0254] Ten samples with a length of 500 mm were prepared for each dipped cord. Then, according to ASTM D885 and ASTM D885M-10a (2014)-test method, a tensile speed of 300 m / min was applied to each sample using an Instron tester (Instron Engineering Corp., Canton, Mass), whereby the stiffness, toughness and elongation at break of each sample were measured respectively. Then, the arithmetic mean values ​​of the stiffness, toughness and elongation at break of the ten samples were calculated respectively.

[0255] [Table 2]

[0256]

[0257] Referring to Table 2, it can be confirmed that the cords of Examples 1 to 4, which include the para-aramid fiber having a large apparent crystal size and a high crystallinity and thus exhibit excellent mechanical properties, have lower creep strain than Comparative Example 1 and have high resistance to external force deformation.

Claims

1. A cord formed by twisting a first primary twist yarn and a second primary twist yarn, wherein: The first pre-twisted yarn is formed by imparting twist to a para-aramid fiber having a crystallinity of 67% or more, an apparent crystal size of 5.8 to 7.0 nm based on a 110 plane, a total fineness of 200 to 1600 deniers, and a tenacity of 22 g / d or more, wherein the second pre-twisted yarn is formed by imparting twist to a different fiber than the para-aramid fiber.

2. The cord according to claim 1, wherein The dissimilar fibers include nylon fibers or polyester fibers. 3 . The cord according to claim 1 , further comprising a coating layer formed on the first and second primarily twisted yarns.

4. The cord according to claim 3, wherein The cord satisfies the creep strain within 3.0%.

5. The cord according to claim 1, wherein: The first pre-twisted yarn is a pre-twisted yarn that imparts a twist of 250 to 600 TPM to the para-aramid fiber. The second primarily twisted yarn is a primarily twisted yarn obtained by imparting a twist of 250 to 600 TPM to the different fibers.

6. The cord according to claim 1, wherein The cord is formed by secondarily twisting the first pre-twisted yarn and the second pre-twisted yarn at a twist number of 250 to 600 TPM.

7. A method for manufacturing a cord, comprising the following steps: Prepare para-aramid fiber having a crystallinity of 67% or more, an apparent crystal size of 5.8 to 7.0 nm based on the 110 plane, a total fineness of 200 to 1600 deniers, and a tenacity of 22 g / d or more; and A first primarily twisted yarn and a second primarily twisted yarn are secondarily twisted together to prepare the cord as a plied yarn, wherein the first primarily twisted yarn is formed by imparting twist to the para-aramid fiber, and wherein the second primarily twisted yarn is formed by imparting twist to a different fiber than the para-aramid fiber.

8. The method for manufacturing a cord according to claim 7, wherein: The dissimilar fibers include nylon fibers or polyester fibers.

9. The method for manufacturing a cord according to claim 7, further comprising forming a coating layer on the plied yarn.

10. The method for manufacturing a cord according to claim 9, wherein: The cord satisfies the creep strain within 3.0%.

11. The method for manufacturing a cord according to claim 7, wherein: The first pre-twisted yarn is produced by imparting a twist of 250 to 600 TPM to the para-aramid fiber, The second pre-twisted yarn is produced by imparting a twist of 250 to 600 TPM to the dissimilar fibers.

12. The method for manufacturing a cord according to claim 7, wherein: The cord is formed by secondarily twisting the first pre-twisted yarn and the second pre-twisted yarn at a twist number of 250 to 600 TPM.

13. The method for manufacturing a cord according to claim 7, wherein: The preparation of the para-aramid fiber comprises: filtering the reaction raw materials to remove impurities; adding an aromatic diamine to a mixed solvent comprising an organic solvent and an inorganic salt to form a slurry; adding an aromatic diacid halide to a reactor comprising the slurry three or more times, and reacting the mixture to form a para-aramid polymer; and spinning a spinning solution comprising the para-aramid polymer to produce fibers, Wherein, in the formation of the para-aramid polymer, during the first addition and the second addition of the aromatic diacid halide, the difference between the cooling water temperature at the cooling water inlet side and the cooling water outlet side for cooling the reactor is controlled within 50°C.

14. The method for manufacturing a cord according to claim 13, wherein: The filtering the reaction raw materials to remove impurities includes filtering the reaction raw materials using a filter having a diameter of 0.01 to 1.0 μm.

15. The method for manufacturing a cord according to claim 13, wherein: During the second addition of the aromatic diacid halide, the stirring speed of the reactor was adjusted to 10 to 1000 rpm.

Citation Information

Patent Citations

  • Cable for tire cord reinforcement

    CN101403154A

  • Creep-resisting ultra-high molecular weight polyethylene fiber hybrid fabric and preparation method thereof

    CN101768809A

  • High linear density, high modulus, high tenacity yarns and methods for making the yarns

    CN101821438A

  • Hybrid fiber cord and method for manufacturing the same

    CN104919099A

  • Hybrid tire cord and method for manufacturing the same

    CN106283307A

Cited By

  • Lightweight high-strength aramid fiber composite cord fabric and production method thereof

    CN121496757A